THE ROLE OF INNOVATION IN BUSINESS DEVELOPMENT - M. N. Mikhaylyuk; M. K. Ashinova; M. A. Omid Karizada (Новые технологии)
A changing world and global trends are both challenges that need to be answered and chances that can be taken by creating and introducing innovations. The results of the survey among the leaders of large companies have shown that more than 80 % of them believe that innovation is the most important factor for success, but less than 10 % are satisfied with the level of innovation development in their company or even deal with this issue [1]. This underlines the relevance of the topic of innovation.The purpose of the article is to assess success factors in the development of innovations, identify obstacles to the realization of the potential of innovations, and suggest tools for developing innovations in terms of speed and scale of transformations by evaluating the effectiveness of companies in innovation. At the same time, modern methods of scientific knowledge are used: analysis, synthesis, induction, abstraction.The article identifies success factors in the development of innovations: innovative strategy and ambitious goal-setting; the broadest search for opportunities; the availability of an appropriate organizational structure and resources – finances, personnel and skills; optimization of the system and management processes; corporate culture and motivation.The redistribution of the budget for research and development costs and the effectiveness of companies in the field of innovation have been considered. In addition, the distribution of portfolio resources by type of innovative activity, the results of which substantiate the choice of innovation tools have been studied.The study of a set of tools, the applicability of which depends on the speed and specifics of the changes has made it possible to identify typical obstacles to the realization of the innovation potential.